First collection of Torrenticolidae (Hydrachnidiae, Acari) from Yintiaoling National Nature Reserve, China, with descriptions of two new species - Gu, Xinyao; Zhang, Yuhao; Zheng, Yuling; Guo, Jianjun (Zootaxa, 2023)
Torrenticolid mites (Hydrachnidiae, Acari) are presented from Yintiaoling National Nature Reserve, China. Torrenticola multiserrater Gu & Guo sp. nov., and T. pseudoalargada Gu & Guo sp. nov. are described and illustrated as new to science; T. siamis Pešić & Smit, 2009 and T. nipponica (Enami, 1940) are reported as new records for Chongqing’s fauna. Meanwhile, this is the first report of Torrenticolidae from Chongqing, China.